Chemical composition and biological activities of essential oil and methanol extract of Scrophularia umbrosa - E. Nikkhah; S. Asnaashari; H. Babaei; F. Heshmati Afshar; A. Delazar (Iranian Society of Pharmacognosy, 2017)
Background and objectives: Scrophularia umbrosa Dumort is used as a traditional herb in China. In this study, chemical profile, free radical suppression capability, general toxicity and cardiovascular activities of the volatile compounds from S. umbrosa were investigated. Moreover, methanol (MeOH) extract of rhizomes were analyzed to purify and identify the constituents.  Methods: GC/MS was used to identify chemical combination of the volatile oil. Suppression of free radicals of the volatile oil was examined by DPPH method. Also, the essential oil was evaluated for its general toxicity and cardiovascular activity using brine shrimp lethality bioassay and organ bath method, respectively. Preparative HPLC and NMR were applied for investigating the MeOH extract composition.  Results: Forty one Ingredients were recognized, displaying about 93.08 % of the total volatile oil constituents Ketones (38.49%) with hexahydrofarnesyl acetone (26.18%), phytol (11.86%), palmitic acid (8.92%), β-damascenone (4.1%) and copaene (3.82%) were the main components. The essential oil showed weak free radical scavenging activity (RC50=13.71±0.75 mg/mL). Relatively high levels of toxicity were observed with the essential oil of S. umbrosa in comparison with podophyllotoxin. Likewise, the essential oil was able to induced vasorelaxantion in isolated rat aortic rings both in presence and absence of endothelium at a similar rate. An iridoid compounds (sesamoside) was isolated from the MeOH extract of S. umbrosa. Conclusion: Chemical diversity is probably responsible for various pharmacological activities. However, the essential oil of this plant showed toxicity in preliminary toxicity test;  so its toxic effect should be more investigated by various cell lines.